Penerapan Audit atas Aset Tetap dalam Menunjang Keandalan Laporan Keuangan - Fika Andriana; Wafia Tamara; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the application of fixed asset audits in supporting the reliability of financial statements. Fixed assets are essential components that influence a company’s financial position and performance, making errors in recognition, measurement, or presentation potentially lead to material misstatements. Using a qualitative, literature-based approach, this study examines audit procedures such as document verification, physical inspection, ownership confirmation, and depreciation testing, all of which ensure the existence, fair valuation, and completeness of disclosures related to fixed assets. The findings indicate that a systematic audit not only detects recording errors and weaknesses in internal control but also enhances the fair representation of financial statements. Therefore, the implementation of a fixed asset audit significantly contributes to improving the reliability of financial information used by stakeholders.